A longitudinal study of corporate social responsibility disclosure amongst insurance companies in Kenya - Naliki, Nkoimu Mary (Strathmore University, 2013)
Most of the extant studies on social accounting have been conducted in developed and advanced economies. Due to differences in the socio-economic context between developed and developing economies, it is essential carry out research on Corporate Social Responsibility Disclosure (CSRD) in developing countries.This is therefore an empirical examination on disclosure of Corporate Social Responsibilty initiatives amongst insurance companies in Kenya where disclosure on social accounting is voluntary. The underlying theory of this study is legitimacy theory. This study has used content analysis and adopted instruments used in prior studies to measure the nature and extent of disclosure on Corporate Social Responsibility in the corporate annual reports of insurance companies during the period 2004 to 2011. The population for this study was drawn from registered insurance companies in Kenya as at 31st December 2012. The results of the study reveal that quite a large proportion of insurance companies made CSRD in the corporate annual reports (CARs) during the period under study. The theme most preferred by insurance companies is community development while the least preferred theme is energy. Insurance companies used a combination of monetary, non-monetary, declarative and pictorial disclosures. Most insurance companies preferred to disclose ' good news' only which may suggest that insurance the companies aim at influencing the public's perception about the companies. The findings of the study suggest that legitimacy theory explains why insurance companies voluntariy make CSRD in their CARs. The findings of the study show that gross premiums written, total assets, ownership structure, existence of board audit committee and return on assets are significantly related to CSRD in the sampled insurance companies in Kenya. Conversely, profit before tax, board composition, size of the audit firm and return on equity are not significantly related to CSRD in the sampled insurance companies. In addition the findings established that gross premiums written, ownership structure, existence of board audit committee, size of audit firm and return on assets are positively associated with CSRD in the sampled insurance companies. On the other hand, total assets , profit before tax, board composition and return on equity are negatively associated with CSRD in the sampled insurance companies.
A thesis submitted to the School of Management and Commerce (SMC) in partial fulfilment of the requirements for the award of a Master of Commerce degree in Strathmore University.
Keywords: Corporate; Social responsibility; Insurance companies; Kenya; Corporate Annual Reports